Changes in acidic soil chemical properties and carbon dioxide emission due to biochar and lime treatments - Mosharrof, Mehnaz; Uddin, Md. Kamal; Jusop, Shamsuddin; Sulaiman, Muhammad Firdaus; Shamsuzzaman, S. M.; Haque, Ahmad Numery Ashfaqul (Multidisciplinary Digital Publishing Institute, 2021)
To mitigate global climate change and simultaneously increase soil productivity, the use of biochar in agriculture can be a modern agro-technology that can help in reducing greenhouse gas emissions, enhancing soil carbon sequestration, and ultimately increasing crop yield. This study aimed to evaluate the effects of biochar and lime application on the chemical properties of acid soil and the emission of CO2. A 60-day incubation study was conducted with eleven treatments (T) in which two different biochar produced from rice husk (RHB) and oil palm empty fruit bunches (EFBB) at two rates (10 and 15 t ha−1) and on three rates of dolomitic limestone (100%, 75%, and 50%), recommended rate of NPK and a control (no amendment). The result showed that biochar and lime significantly increased soil pH, available P, and decreased exchangeable Al compared to the control. The pH increase was 44.02% compared to the control treatment on day 15, and the available P was found to be 22.44 mg kg−1 on day 30 from Treatment 7 (75% lime + 15 t ha−1 RHB). The cumulative CO2 emission from T7 was 207.40 μmol CO2 m−2 that decreased 139.41% compared to the control. Our findings conclude that RHB with 75% lime has more potential than EFBB to increase nutrient availability and reduce the emission of CO2 in acid soil.